Strengthening personality traits to promote Iban women's empowerment and tourism in Sarawak - Yaccob, Yasmin; Mat Jusoh, Nurul Hidayu; Adam Assim, Mohd Ibrani Shahrimin; Md Saad, Juniza (Human Resource Management Academic Research Society, 2023)
Tourism has a vital role to play in achieving Sustainable Development Goals, especially in the empowerment of women. To enhance the positive impact of tourism development on women’s lives, initiatives to intensify personality traits and skills competencies need to be emphasized. Iban women are the majority ethnic group in Sarawak who were involved in economic activities and tourism. This paper aims to assess personality traits and improve skills competencies as a tourism agenda to empower Iban Women in Sarawak. The socio-economic status of Iban women in rural areas can be uplifted via tourism-related programs. This study uses a quantitative approach with a descriptive design through questionnaire form, which is a modified instrument of the Big Five and Competencies Skills that will refer to generic knowledge, skills, and attitudes. A total of 190 Iban women aged 18 and above were involved as respondents. Ultimately, Iban women had high consciousness traits (F = 4.31). The trait indicates that Iban Women are committed to working as well as responsible, dependable, and trustworthy. The production of traditional handicrafts is the main skill of Iban Women in Sarawak who contribute to the state’s economic growth and tourism development. The Iban woman not only plays a major role in supplementing income to their household in a far-off rural community but also enhances the preservation and conservation of the authentic culture of the Iban community. Further studies are suggested to include more indicators for enhancing Iban women empowerment initiatives.